Entering unknown territory : exploring the impact on indigenous field researchers when conducting gender based violence and child abuse research in the Solomon Islands : a thesis presented in partial fulfillment of the requirements for the degree Master of Philosophy in Social Work, Massey University, New Zealand - Titchener, Sharyn (Massey University, 2010)
This study explores the reflective experiences of indigenous field researchers who were involved in conducting the first population representative research study on gender-based violence and child abuse in the Solomon Islands. The purpose of this thesis study was to gain an understanding and insight into the field researchers’ perceptions of the positive and negative impacts such involvement may have had on their lives. The term ‘impact’ was applied holistically and focus was given to whether negative impacts were mitigated by the positive benefits that may be present from being involved in such research. The research study design was exploratory and qualitative in nature, underpinned by a phenomenological approach. The participants were 29 Solomon Island women who had been employed in the role of ‘field researcher’ for the Solomon Island Family Health and Safety Study. Data collection methods included the use of both in-depth interviews and focus group discussions. Eleven interviews were conducted using a semi-structured approach. Three focus group discussions were facilitated, with the assistance of an open-ended questionnaire guideline. The findings identified a number of themes that emerged from the data collected. The themes highlighted primary impacts that included an emotional, physical and life-changing dimension. There was a pattern where different themes were more prevalent, dependent on what phase of the ‘research journey’ that the researchers’ were reflecting on. A significant finding was that although field researchers’ primarily reported negative impacts, they all unanimously stated that they would be interested in being involved in conducting research on violence against women and children in the future. These findings not only suggest that the positive benefits from being involved in such research mitigated the many negative impacts as reported by the field researchers, but also suggest that through being involved with such research, they developed an increased commitment within their own communities to assist in reducing violence against women and children. Conducting research on violence against women and children in a developing post-conflict country brings with it many physical and emotional challenges for indigenous field researchers. It is essential that field researchers are provided with considerable support during all phases of the research study. The application of ethical and safety standards needs to reflect the unique characteristics of the country where the study is being conducted, taking into account the situational and ambient dangers that field researchers may be confronted with during their time in the field.
Keywords: Indigenous researchers; Solomon Islands; Family violence; Fields of Research::370000 Studies in Human Society::379900 Other Studies In Human Society::379902 Indigenous studies